The source altitude, electric current, and intrinsic brightness of terrestrial gamma ray flashes. Issue 23 (2nd December 2014) - Cummer, Steven A.; Briggs, Michael S.; Dwyer, Joseph R.; Xiong, Shaolin; Connaughton, Valerie; Fishman, Gerald J.; Lu, Gaopeng; Lyu, Fanchao; Solanki, Rahulkumar
Abstract: Many details of how thunderstorms generate terrestrial gamma ray flashes (TGFs) and other forms of high‐energy radiation remain uncertain, including the basic question of where they are produced. We exploit the association of distinct low‐frequency radio emissions with generation of terrestrial gamma ray flashes (TGFs) to directly measure for the first time the TGF source altitude. Analysis of two events reveals source altitudes of 11.8 ± 0.4 km and 11.9 ± 0.9 km. This places the source region in the interior of the thunderstorm between the two main charge layers and implies an intrinsic TGF brightness of approximately 10 18 runaway electrons. The electric current in this nontraditional lightning process is found to be strong enough to drive nonlinear effects in the ionosphere, and in one case is comparable to the highest peak current lightning processes on the planet. Key Points: TGFs are produced near 12 km between the charge layers of a thunderstorm TGFs contain approximately 10 18 runaway electrons The electric current in the TGF generation process can be very strong